Combining CSPG4-CAR and CD20-CCR for treatment of metastatic melanoma - Teppert, Karin; Winter, Nora; Herbel, Vera; Brandes, Caroline; Lennartz, Simon; Engert, Fabian; Kaiser, Andrew; Schaser, Thomas; Lock, Dominik (Frontiers in immunology, 2023)
The prognosis for patients with metastatic melanoma is poor and treatment options are limited. Genetically-engineered T cell therapy targeting chondroitin sulfate proteoglycan 4 (CSPG4), however, represents a promising treatment option, especially as both primary melanoma cells as well as metastases uniformly express CSPG4. Aiming to prevent off-tumor toxicity while maintaining a high cytolytic potential, we combined a chimeric co-stimulatory receptor (CCR) and a CSPG4-directed second-generation chimeric antigen receptor (CAR) with moderate potency. CCRs are artificial receptors similar to CARs, but lacking the CD3ζ activation element. Thus, T cells expressing solely a CCR, do not induce any cytolytic activity upon target cell binding, but are capable of boosting the CAR T cell response when both CAR and CCR engage their target antigens simultaneously. Here we demonstrate that co-expression of a CCR can significantly enhance the anti-tumor response of CSPG4-CAR T cells in vitro as well as in vivo . Importantly, this boosting effect was not dependent on co-expression of both CCR- and CAR-target on the very same tumor cell, but was also achieved upon trans activation. Finally, our data support the idea of using a CCR as a powerful tool to enhance the cytolytic potential of CAR T cells, which might open a novel therapeutic window for the treatment of metastatic melanoma.